Early vedolizumab trough levels predict mucosal healing in inflammatory bowel disease: a multicentre prospective observational study. Issue 7 (31st January 2018) - Yacoub, W.; Williet, N.; Pouillon, L.; Di‐Bernado, T.; De Carvalho Bittencourt, M.; Nancey, S.; Lopez, A.; Paul, S.; Zallot, C.; Roblin, X.; Peyrin‐Biroulet, L.
Summary: Background: The correlation between vedolizumab trough levels during induction therapy and mucosal healing remains unknown. Aim: To compare early vedolizumab trough levels in patients with and without mucosal healing within the first year after treatment initiation. Methods: We prospectively collected vedolizumab trough levels in all inflammatory bowel disease patients at weeks 2, 6 and 14 of vedolizumab treatment in three French referral centres between 1 June 2014 and 31 March 2017. Results of every patient that underwent mucosal assessment by magnetic resonance imaging and/or endoscopy in the first year after treatment initiation were analysed. Results: Median vedolizumab trough levels in the overall population (n = 82) were 27 μg/mL (interquartile range, IQR 21.2‐33.8 μg/mL) at week 2, 23 μg/mL (IQR 15‐34.5 μg/mL) at week 6 and 10.7 μg/mL (IQR 4.6‐20.4 μg/mL) at week 14. Only median vedolizumab trough levels at week 6 differed between patients with and without mucosal healing within the first year after treatment initiation (26.8 vs 15.1 μg/mL, P  =   0.035). A cut‐off trough level of 18 μg/mL at week 6 predicted mucosal healing within the first year after the start of vedolizumab with an area under the receiver operating curve of 0.735 (95% confidence interval 0.531‐0.939). A vedolizumab trough level above 18 μg/mL at week 6 was the only independent variable associated with mucosal healing within the first year of treatment (odds ratio 15.7, 95% confidence interval 2.4‐173.0, P  =   0.01). Conclusion: Early therapeutic drug monitoring might improve timely detection of vedolizumab‐treated patients in need for an intensified dosing regimen. Abstract : Linked Content This article is linked to Fragaki and Karmiris and Marabotto papers. To view these articles visithttps://doi.org/10.1111/apt.14588 andhttps://doi.org/10.1111/apt.14800 .